Efeitos de dois métodos de resfriamento corporal sobre variáveis psicofisiológicas de indivíduos com tetraplegia submetidos a uma sessão de exercício aeróbio em ambiente quente - Ingrid Ludimila Bastos Lôbo (2023)
Individuals with tetraplegia due to spinal cord injury (SCI) have dysfunction of the sympathetic nervous system, including thermoregulatory responses. Thus, in hot environments or during physical exercise, anhidrosis and inadequate regulation of skin blood flow occur, impairing the maintenance of thermal homeostasis. Because of this, different cooling strategies have been evaluated to attenuate the rise in body temperature and reduce thermal discomfort in quadriplegics. This study aimed to analyze the effects of two methods of body cooling on physiological responses (body temperatures and heart rate), subjective perception of exertion, and thermal perception (comfort and thermal sensation) during an aerobic exercise session in a hot environment. Nine male subjects (37.7 ± 6.5 years) with SCI between segments C5 and T1, classified as quadriplegic, voluntarily participated in this investigation. Volunteers performed 30 minutes of exercise on an arm cycle ergometer (submaximal intensity of 65% of aerobic power) and 30 minutes of recovery in three different experimental conditions: control (CON), cooling vest (CLT), and spraying water on the skin (PUL). The experiments were carried out in an environmental chamber with a temperature of 32ºC and relative humidity between 50-60%. Core temperature (TC) was measured using an ingestible telemetry pill and peripheral temperature (TP) was measured using an infrared digital thermometer (chest, arm, thigh, and leg). Heart rate (HR), perceived exertion (PSE), thermal comfort (CT), and thermal sensation (ST) were also measured. Two-way ANOVA (experimental conditions vs. exercise or recovery time) with repeated measures and Tukey's post hoc were used for inferential analyses. Effects of CLT and PUL conditions on the reduction of TC during exercise were not demonstrated, whose temperature averages were 37.39 ºC and 37.45 ºC, respectively. Similarly, in the post-exercise period, no effects of CLT and PUL conditions were verified on CT, whose values were 37.86ºC and 37.75ºC. However, PUL was effective in reducing PT in both phases, compared to CON and CLT conditions, with exercise values being 34.81 ºC (CON); 34.16 ºC (CLT), and 32.25 ºC (PUL) and post-exercise, 35.74 ºC, 35.33 ºC and 32.98 ºC, respectively. About the HR, lower values were verified in the PUL in the post-exercise (77 bpm), in comparison with the conditions WITH (84 bpm) and CLT (81 bpm). Both cooling conditions had effects on PSE, whose values were lower compared to the CON condition. Regarding CT and ST, both in exercise and post-exercise, significant differences were observed in PUL and CLT conditions, indicating better thermal perception in both. The results of this study indicate that CLT and PUL have beneficial effects on RPE, CT, and ST during aerobic exercise and recovery. The PUL condition proved to be effective in mitigating the increase in PT during exercise and recovery, indicating that this strategy favors evaporative cooling from the skin of individuals with SCI. It is estimated that both conditions can prolong the time of tolerance to physical exercise in hot environments.